ROS1 Expression and Histopathological Grading in Non-Small Cell Lung Cancer Patients at Tertiary Hospitals in Medan, Indonesia - Nurul Syuhada Parinduri; Noni Novisari Soeroso; Desfrina Kasuma; Putri Chairani Eyanoer; Darren Wan-Teck Lim (Faculty of Medicine Universitas Airlangga, 2026)
Introduction: Lung cancer remains the leading cause of cancer-related mortality worldwide, with most cases classified as non-small cell lung cancer (NSCLC). Genetic alterations in epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), Kirsten rat sarcoma viral oncogene homolog (KRAS), mesenchymal-epithelial transition (MET), and c-ros oncogene 1 (ROS1) play important roles in guiding targeted therapy strategies. This study aimed to evaluate ROS1 expression in patients with histopathologically confirmed NSCLC and to determine its association with histopathological grading and tumor subtype. Methods: This analytical observational study employed a cross-sectional design using 120 paraffin-embedded tissue samples obtained from NSCLC patients at several hospitals in Medan, Indonesia, between March 2024 and March 2025. Associations were analyzed using the Chi-square test, with p<0.05 considered statistically significant. Results: Adenocarcinoma was the predominant histopathological subtype, accounting for 75% of cases. Positive ROS1 expression was identified in 64.2% of patients. A significant association was observed between ROS1 expression and histopathological grading (p=0.048), whereas no significant association was found between ROS1 expression and histopathological subtype (p=0.742). Receiver operating characteristic (ROC) analysis demonstrated limited diagnostic performance of ROS1 expression, with an area under the curve (AUC) value of 0.451. Conclusion: The ROS1 expression was significantly associated with histopathological grading but showed no correlation with histopathological subtype in NSCLC patients. The ROS1 immunohistochemistry may serve as a practical screening tool in NSCLC, although its diagnostic performance remains limited.